Prognostic value of Alzheimer's disease plasma biomarkers in the oldest-old: a prospective primary care-based study - Adami, Pamela V. Martino; Chatterjee, Madhurima; Kleineidam, Luca; Weyerer, Siegfried; Bickel, Horst; Wiese, Birgitt; Riedel-Heller, Steffi G.; Scherer, Martin; Blennow, Kaj; Zetterberg, Henrik; Wagner, Michael; Schneider, Anja; et al. (The lancet. Regional health, 2024)
Background - Blood-based biomarkers offer a promising, less invasive, and more cost-effective alternative for Alzheimer's disease screening compared to cerebrospinal fluid or imaging biomarkers. However, they have been extensively studied only in memory clinic-based cohorts. We aimed to validate them in a more heterogeneous, older patient population from primary care. - Methods - We measured plasma Aβ42/Aβ40, P-tau181, NfL, and GFAP in 1007 individuals without dementia, aged 79-94 years, from the longitudinal, primary care-based German AgeCoDe study. We assessed the association with cognitive decline, disease progression, and the capacity to predict future dementia of the Alzheimer's type (DAT). We also evaluated biomarker dynamics in 305 individuals with a follow-up sample (∼8 years later). - Findings - Higher levels of P-tau181 (HR = 1.32 [95% CI: 1.17-1.51]), NfL (HR = 1.19 [95% CI: 1.03-1.36]), and GFAP (HR = 1.36 [95% CI: 1.22-1.52]), and a lower Aβ42/Aβ40 ratio (HR = 0.80 [95% CI: 0.68-0.95]) were associated with an increased risk of progressing to clinically-diagnosed DAT. Additionally, higher levels of P-tau181 (β = −0.49 [95% CI: −0.71 to 0.26]), NfL (β = −0.29 [95% CI: −0.52 to 0.06]), and GFAP (β = −0.60 [95% CI: −0.83 to 0.38]) were linked to faster cognitive decline. A two-step DAT prediction strategy combining initial MMSE with biomarkers improved the identification of individuals in the prodromal stage for potential treatment eligibility. Biomarker levels changed over time, with increases in P-tau181 (β = 0.19 [95% CI: 0.14-0.25]), NfL (β = 2.88 [95% CI: 2.18-3.59]), and GFAP (β = 8.23 [95% CI: 6.71-9.75]). NfL (β = 2.47 [95% CI: 1.04-3.89]) and GFAP (β = 4.45 [95% CI: 1.38-7.51]) exhibited a faster increase in individuals progressing to DAT. - Interpretation - Evaluating plasma biomarkers, alongside brief cognitive assessments, might enhance the precision of risk assessment for DAT progression in primary care. - Funding - Alzheimer Forschung Initiative, Bundesministerium für Bildung und Forschung.
Online verfügbar: 16. August 2024
Gesehen am 12.11.2024